WEBSITES PRACTICING TO DEVELOP LISTENING SKILLS - Citra Kusumaningsih; Senny Wiyanti; Yulia Ramadhiyanti (Jurnal Pendidikan Bahasa, 2019)
This paper shows the qualitative study of the employment of websites to practice English listening skills of students. The samples in this survey were the students majoring in English, one of school education, Pontianak, Indonesia. The open-ended questionnaire and interview were used to compile the data. The study reported that the students held a positive attitude toward the use of the websites for practicing listening skills because of many advantages such as the websites offer unlimited opportunities to learn and practice their listening skill as if they are in the real situation with native speakers and these opportunities provided them more new English vocabularies. Moreover, it can facilitate them to create autonomous learning strategies. It was also found that it was so convenient when using the internet sites for practicing listening skills outside classroom and from book, anywhere and anytime. However, the students experienced a problem with the native speaker accent so they could not understand the conversation.